Alicia Berenson’s Complex Post-Traumatic Stress Disorder in Alex Michaelides’ The Silent Patient - Amelia Pratiwi; Tri Pramesti (CV Wahana Publikasi, 2022)
This study examines the psychiatric symptoms called Complex Post-Traumatic Stress Disorder (PTSD) experienced by Alicia Berenson in The Silent Patient by Alex Michaelides. This study aims to describe the symptoms and causes of Alicia Berenson, who experienced Post-Traumatic Stress Disorder (PTSD). In this study, the writer applies a theory of the psychology of literature by Wellek and Warren and the theory of PTSD by Carlson & Ruzek. This study uses a psychological approach. The method used is descriptive qualitative. There are several PTSD symptoms found in Alicia’s characters, i.e., reliving the trauma through flashbacks, negative self-view, aggressive behavior toward oneself or others, impulsive behavior, social isolation, emotional regulation, and relationship difficulty. The causes of Alicia’s PTSD are a car accident at a young age, verbal abuse, sexual abuse, child abuse, and betrayal by her husband. It can be concluded that Alicia experienced PTSD, which later became complex PTSD due to repeated verbal abuse over a long period.